(untitled) (Acta Scientiarum. Language and Culture, 2026)
This research investigates processes related to European colonialism through the analysis of the Guyanese novel Corentyne Thunder (2009/1941) by Edgar Mittelholzer, with particular attention to the elements that portray the peasant life of its protagonist, Ramgolall, an old Indian immigrant and indentured laborer. The study sought to interpret Ramgolall’s relationship with his past and with the money accumulated in his ‘canister’ over the course of his life, which has been marked by significant privations he imposed on himself and his family. To this end, the research draws on a theoretical framework on colonialism, primarily Black Skin, White Masks (Fanon, 2020), Colonialism/Postcolonialism (Loomba, 2005), and Colonial and Postcolonial Literature (Boehmer, 2005), as well as on studies of migration history in what was then British Guiana, such as Aspects of Primitivism in the West Indian Novel of the 1930s (Macintosh, 2008) and Demographic Change in Nineteenth-Century Guyana (Mcgowan, 2005). This framework allows for situating the Indian cow-minder’s family within the broader social conditions of these immigrants after their years of indentured labor. The analysis reveals that Mittelholzer’s novel, published under imperial license, articulates discussions that exceed the discursive control of colonialism by delving deep into the intimate and particular experiences of this family nucleus. In this confrontation, Ramgolall’s obsessive accumulation of money in his ‘canister’ emerges as a fictional representation of the pathology of peripheral cultural identity in the face of oppression by a violent ‘center’, not through military means but through the symbolic paths of subalternity and silence.